2017
DOI: 10.1097/aln.0000000000001433
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Methylprednisolone on Postoperative Quality of Recovery and Delirium in the Steroids in Cardiac Surgery Trial

Abstract: Background Inflammation after cardiopulmonary bypass may contribute to postoperative delirium and cognitive dysfunction. The authors evaluated the effect of high-dose methylprednisolone to suppress inflammation on the incidence of delirium and postoperative quality of recovery after cardiac surgery. Methods Five hundred fifty-five adults from three hospitals enrolled in the randomized, double-blind Steroids in Cardiac Surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 24 publications
1
54
1
1
Order By: Relevance
“…Therefore, it is widely used to treat a variety of acute and chronic inflammatory diseases including acute lung inflammation, asthma, and rheumatoid arthritis [1]. A number of studies have been reported for the anti-inflammatory properties of MP [24]. For instance, MP induces anti-inflammatory cytokines expression such as IL-10.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is widely used to treat a variety of acute and chronic inflammatory diseases including acute lung inflammation, asthma, and rheumatoid arthritis [1]. A number of studies have been reported for the anti-inflammatory properties of MP [24]. For instance, MP induces anti-inflammatory cytokines expression such as IL-10.…”
Section: Introductionmentioning
confidence: 99%
“…At the time of study design and sample size calculation, the presence of preoperative baseline cognitive frailty in elderly patients was unrecognized. Subsequently, 32%‐51% of patients in clinical trials were found to have cognitive frailty . The PostopQRS test terminology classifies this as low baseline cognition, which occurred in 42% of patients in our study.…”
Section: Discussionmentioning
confidence: 74%
“…Another possible limitation is the presence of delirium. In a recent study, patients with delirium diagnosed using the Confusion Assessment Method had significantly worse PostopQRS cognitive recovery over the first three postoperative days than patients who were not delirious . Although not formally evaluated, the diagnosis of delirium is not incompatible with our study aim.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations